RELATIONSHIP OF TOTAL OIL CONTENT WITH EPIPELIC DIATOMS ABUDANCE IN INTERTIDAL SEDIMENT IN THE WATER OF KUALA TANJUNG BATUBARA DISTRICT NORTH SUMATERA PROVINCE - Mutiara, Dhea Esa; Amin, Bintal; H. Siregar, Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbtracA study on the effect of total oil content on the epipelic diatom abundance were done in January to March 2018 in The Intertidal Zone of Kuala Tanjung Batubara District North Sumatera. Sediment samples were taken from 4 stations with different activities  and each stations was divided based on the intertidal zone (upper, middle, andlower). The result showed that total oil content the highest was station 4 (5377,1986 ppm)and the lowest was at station 2 (142,8497ppm).The highest abundance of epipelic diatom was found at station 2 (8933 ind/cm2).Epipelic diatom that were found in the intertidal zoneof Kuala Tanjung composing of 14 spesies. The total oil content in the intertidal zone was not different and total oil content between station was different. The epipelic diatom abundancein the intertidal zone was not differentand epipelic diatom abundance between station was different. Relationships between total oil content with epipelic diatom abundance in Kuala Tanjung were y= 7234,5 - 1570,7x; R2= 0,7432; r = 0,86. The oil content and epipelic diatom abundance has negative correlation, which means in creasing of oil content will cause a decrease the abundance of epipelic diatom in Kuala Tanjung. Keyword: In The Water of  Kuala Tanjung, Total Oil Content, Epipelic Diatom, Pollution